Examination of Structural Variations of the Circle of Willis by 3D Time-of-Flight Magnetic Resonance Angiography - Jing Li; Jue Wang; Xiao-er Wei; Yu-wu Zhao; Feng Wang; Yue-hua Li (Frontiers in Neuroscience, 2020)
Objectives: To explore structural variations of the circle of Willis using three-dimensional time-of-flight magnetic resonance angiography (3D-TOF-MRA), and to compare this modality with digital subtraction angiography (DSA).Methods: A total of 819 consecutive patients suspected of having cerebral vascular diseases underwent 3D-TOF-MRA, followed by DSA within 2 weeks. We report accuracy, sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of 3D-TOF-MRA compared with DSA.Results: The sensitivity and specificity of combined analyses were 90–100 and 98–100%, respectively. The sensitivity and NPV of 3D-TOF-MRA images for A-, C-, D-, and H-types of circle of Willis anomalies were 100%. The specificity, accuracy and sensitivity were all 100% for detecting absence of the anterior communicating artery (ACOA). Sensitivity, specificity, PPV, and NPV were all 100% for detecting F-type. The sensitivity and PPV of volume rendered (VR) images for the B-, E-, and G-types were relatively low (85.0, 86.2, and 73.8%, respectively). Maximum intensity projection (MIP) was somewhat better (88.3, 89.2, and 81.8%, respectively). Combined analyses were better still (95.8, 96.1, and 99.0%, respectively). Specificity and NPVs were high (99.3–100%).Conclusions: 3D-TOF-MRA compares well to DSA for evaluation of the structure of the circle of Willis. As 3D-TOF-MRA is a non-invasive modality, it may be preferred as a means to evaluate structural variations of the circle of Willis.